P108 Pharmacokinetics of mycophenolic acid for systemic lupus erythematosus in children. Issue 6 (17th May 2019) - Zhang, D; Elie, V; Magreault, S; Melki, I; Baudouin, V; Jacqz-Aigrain, E
Abstract : Background: Mycophenolate mofetil (MMF) is increasingly used in children with systemic lupus erythematosus (SLE). Monitoring of its active metabolite, mycophenolic acid (MPA), is performed for individual dosage adjustment of MMF and is based on determination of area under the plasma concentration-time curve (AUC12h ) of MPA. The objective of this monocentric study is to describe the pharmacokinetics (PK) of MPA in paediatric patients with SLE or lupus nephritis. Methods: Patients with lupus treated by MMF between January 2009 and July 2018 were included. MPA plasma concentrations (T0, T0.5h, T1h, T2h, T3h, T8h and T12h) were determined by EMIT (enzyme-multiplied immunotechnique) and MPA AUC12h calculated according to trapezoid rule. Results: Twenty-two patients were diagnosed with lupus at 11.5 ± 2.9 years. Clinical presentation was SLE (n=18) or isolated lupus nephritis (n=4). Treatments prior to MMF were steroids and/or immunosuppressants (endoxan, rituximab). Age at initiation of MMF (Cellcept®n=20, Myfortic®n=2) was 12.9 ± 2.6 years. PK of MPA was performed after 8.2 ± 14.8 months of treatment, under MMF dose of 840 ± 218 mg (577 ± 98 mg/m 2 ). A large interindividual variability in MPA concentration-time profiles was observed with the following mean parameters: Cmax =4.60 ± 11.70 µg/mL, tmax =80 ± 77 min, trough plasma concentration (C0 ) = 2.30 ± 1.60 µg/mL and AUC0-12h =46.29 ± 17.39 µg*h/mL. Conclusion: Data on the PK of MPA in lupus children are limited. Our results show the high interindividual variability in MPA exposure after oral administration of MMF. Monitoring of exposure based on AUC in combination with immunological disease parameters will allow to individualise treatment to optimise Disclosure(s): Nothing to disclose